Microclimatic edge-to-interior gradients of European deciduous forests - Meeussen, Camille; Govaert, Sanne; Vanneste, Thomas; Bollmann, Kurt; Brunet, Jörg; Calders, Kim; Cousins, Sara A.O.; De Pauw, Karen; Diekmann, Martin; Gasperini, Cristina; Hedwall, Per-Ola; Hylander, Kristoffer; et al. (Agricultural and forest meteorology, 2021)
•We quantified evaporation and soil and air temperature offsets in forest edges across Europe.•Roughly 10% of European broadleaved forests are affected by altered temperature regimes.•Macroclimate and management affected edge-to-interior temperature offset gradients.•Forest structure and the forest-floor biomass are important drivers of temperature offsets.•Dense forest edges can help mitigate edge influences and protect forest interior microclimates. Global forest cover is heavily fragmented. Due to high edge-to-surface ratios in small forest patches, a large proportion of forests is affected by edge influences involving steep microclimatic gradients. Although forest edges are important ecotones and account for 20% of the global forested area, it remains unclear how biotic and abiotic drivers affect forest edge microclimates at the continental scale. Here we report soil and air temperatures measured in 225 deciduous forest plots across Europe for two years. Forest stands were situated along a latitudinal gradient and subject to a varying vegetation structure as quantified by terrestrial laser scanning. In summer, the average offset of air and soil temperatures in forest edges compared to temperatures outside the forest amounted to -2.8 °C and -2.3 °C, respectively. Edge-to-interior summer temperature gradients were affected by the macroclimate and edge structure. From the edge onwards, larger offsets were observed in dense forest edges and in warmer, southern regions. In open forests and northern Europe, altered microclimatic conditions extended deeper into the forest and gradients were steeper. Canopy closure and plant area index were important drivers of summer offsets in edges, whereas in winter also the forest-floor biomass played a key role. Using high-resolution maps, we estimated that approximately 10% of the European broadleaved forests would be affected by altered temperature regimes. Gradual transition zones between forest and adjacent lands are valuable habitat types for edge species. However, if cool and moist forest interiors are desired, then (i) dense and complex forest edges, (ii) an undisturbed forested buffer zone of at least 12.5 m deep and (iii) trees with a high shade casting ability could all contribute to an increased offset. These findings provide important guidelines to mitigate edge influences, to protect typical forest microclimates and to adapt forest management to climate change.